Older adults with frailty syndrome present an altered platelet function and an increased level of circulating oxidative stress and mitochondrial dysfunction biomarker GDF-15 - Arauna, Diego; Garcia, Francisco; Rodriguez-Manas, Leocadio; Marrugat, Jaume; Saez, Claudia; Alarcon, Marcelo; Wehinger, Sergio; Espinosa Parrilla, Maria Yolanda; Palomo, Ivan; Fuentes, Eduardo (My University, 2020)
Introduction: The elderly population is increasing worldwide and in Chile, it is expected to grow rapidly. The World Health Organization (WHO) ICOPE guideline (Integrated Care for Older People) emphasizes the importance of frailty diagnosis to prevent dependence. Frailty in older adults is considered an indicator of vulnerability and poor health outcomes, of multifactorial etiology. Our objective was to investigate the association of activation of coagulation and increased risk of thrombosis with frailty in people older than 64 years. A prevalent-case control study was designed with 28 frail older and 27 robust older adults (non-frail, control group) older than 64 years. Frailty was defined by Fried's Phenotype, Platelet aggregation and activation plasma levels of Thromboxane B2 (TXB2), 8-isoprostane and Growth Differentiation Factor-15 (GDF-15) were determined. Results: Compared to healthy controls, frail older adults, had a) higher percentage of platelet aggregation induction with ADP 4 mu M (82.85% (3.35) and 73.41% (3.26), p-value = 0.024) and subaggregant dose of ADP (30.83% (7.47) and 13.25% (3.21), p-value = 0.002); b) higher platelet activation: P-selectin exposure (18.23% (4.41) and 6.96% (1.08), p-value = 0.011), and activated GPII beta-III alpha (21.51% (3.41) and 8.26% (1.18), p-value = 0.001), at the baseline level and against a subaggregant dose ADP: P-selectin exposure (46.93% (5.95) and 13.41% (3.35), p-value = 0.002) and activated GPII beta-III alpha (43.29% (6.04) and 26.71% (4.92), p-value = 0.024); c) higher plasma levels of TXB2 (201.8 ng/mL (59.53-236.3) and 45.77 ng/mL (25.14-98.26), p-value < 0.0001), d) elevated plasma levels of 8-isoprostane (70.94 pg/mL, IQ: 65.89-99,96 and 56.24 pg/mL, IQ: 42.18-74.81, p-value = 0.001), and e) higher plasma GDF-15 levels (2,379 pg/mL, IQ: 1,845-4,121 and 1367 pg/mL, IQ: 1190-1747, p-value = 0.0001). Discussion: Older adults with frailty syndrome have an upregulated platelet activity that may contribute to an increased risk of thrombosis and aspirin resistance. The elevated oxidative stress and increases of GDF-15 levels might be related to altered platelet responsiveness in frail patients. Conclusion: The determination of biomarkers of platelet dysfunction, oxidative stress and cell senescence/mitochondrial dysfunction may contribute to frailty diagnosis, and approaches aimed at regulating platelet function in frail older adults could contribute to its prevention and treatment.
Keywords: frailty; aging; platelet; mitochondrial dysfunction; oxidative stress